Sonny boy - Brown, Lew and DeSylva, B. G. and Henderson, Ray and Jolson, Al (Robert Cushman collection of sheet music, 1928)
1 vocal score (5 p.) ; 31 cm. Illustrated cover with images of Al Jolson and Davey Lee.
https://katalog.adlr.link/Record/finc-103-b2FpOmNkbTE1NzU5LmNvbnRlbnRkbS5vY2xjLm9yZzpwMTU3NTljb2xsNi8yMzYw